The Omega Point as Eschaton: Answers to Pannenberg's Questions for Scientists - Tipler, Frank J. (Zygon, 1989)
Abstract. I present an outline of the Omega Point theory, which is a model for an omnipresent, omniscient, omnipotent, evolving, personal God who is both transcendent to spacetime and immanent in it, and who exists necessarily. The model is a falsifiable physical theory, deriving its key concepts not from any religious tradition but from modern physical cosmology and computer science; from scientific materialism rather than revelation. Four testable predictions of the model are given. The theory assumes that thinking is a purely physical process of the brain, and that personality dies with the brain. Nevertheless, I show that the Omega Point theory suggests a future universal resurrection of the dead very similar to the one predicted in the Judeo-Christian-Islamic tradition. The notions of “grace” and the “beatific vision” appear naturally in the model.